2019
DOI: 10.1093/labmed/lmz006
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Biclonal Gammopathy: A Pathologist’s Perspective

Abstract: Background The production of 2 monoclonal proteins characterizes biclonal gammopathic manifestations (BGMs). The available medical literature from India is chiefly restricted to case reports. Objective To study the incidence of BGMs in a tertiary care center in Chandigarh, India, during a 4-year period. We evaluated these cases further for their laboratory characteristics. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…On a similar line, Corradini et al identified pre‐CSR B‐cells carrying the same IGH clonotypic rearrangement of myeloma cells but expressing μ chains 24 . The presence of a pre‐CSR MM precursor would also provide the biological basis for the rare condition of bi‐clonal gammopathies, which have been described in several reports 24–26 . Other groups have described memory B‐cells recirculating through lymph nodes and peripheral blood with homing/spreading capacity through the BM carrying the MM‐specific clonotypic rearrangement 27,28 .…”
Section: From the Cell Of Origin To Pre‐malignant Stagesmentioning
confidence: 87%
See 1 more Smart Citation
“…On a similar line, Corradini et al identified pre‐CSR B‐cells carrying the same IGH clonotypic rearrangement of myeloma cells but expressing μ chains 24 . The presence of a pre‐CSR MM precursor would also provide the biological basis for the rare condition of bi‐clonal gammopathies, which have been described in several reports 24–26 . Other groups have described memory B‐cells recirculating through lymph nodes and peripheral blood with homing/spreading capacity through the BM carrying the MM‐specific clonotypic rearrangement 27,28 .…”
Section: From the Cell Of Origin To Pre‐malignant Stagesmentioning
confidence: 87%
“…24 The presence of a pre-CSR MM precursor would also provide the biological basis for the rare condition of bi-clonal gammopathies, which have been described in several reports. [24][25][26] Other groups have described memory B-cells recirculating through lymph nodes and peripheral blood with homing/spreading capacity through the BM carrying the MM-specific clonotypic rearrangement. 27,28 Besides confirming a GC origin of MM, these studies highlighted the possibility that the aberrant plasma cell clone in MM is repopulated from phenotypically distinct "stem" cells.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with double monoclonal gammopathic manifestations (DMGMs) can express two different M proteins that differ based on the presence of heavy chain (HC) isotypes with the same light chains (LCs) or LC isotypes with the same HC isotype (16). Our patient exhibited DMGMs (IgA κ and IgG κ).…”
Section: Discussionmentioning
confidence: 92%
“…Sharma et al reported a rate of 1.6% (15/916). [ 8 ] Meanwhile, Kyle et al reported a rate of 1.5% (57/3447), [ 9 ] but since they did not include the BG patients with Bence Jones proteinemia, the actual rate may be higher. The frequency reported by Guastafierro et al was 4% (49/1214), [ 10 ] but they excluded cases of double IgA-κ and double IgA-λ, citing the possibility of false positives due to IgA glycosylation and its tendency to polymerize.…”
Section: Discussionmentioning
confidence: 99%